Usable Prospects of Artificial Intelligence (AI) & Ethical Insinuations at the Tertiary Education: An Authentic Estimation of Academia Instructors in Bangladesh: Potensi Penggunaan Kecerdasan Buatan (AI) & Isu Etika dalam Pendidikan Tinggi: Penilaian Otentik dari Para Pengajar Akademik di Bangladesh - Islam, Mainul; Afrin, Mithila (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2025)
This tangible observation explores the opinions of EFL teachers at Bangladeshi public and private institutions regarding the usage of ChatGPT and other AI. This study scrutinized and juxtaposed the opinions of 25+25=50 EFL faculties regarding the trials and potential values of adding AI skills into EFL classes through semi-structured interviews. The key objectives are to enhance AI addition, to highlight ethical concerns and contextualize human-centered issues, and to assess the viewpoints of 25+25=50 university faculty members on the application of AI in EFL training. The research suggests a qualitative approach where the faculty members at private universities employ AI technology more frequently rather than peers at public universities. Even the outcomes of AI learning, everyone agrees that AI can help learners better, there are also concerns about plagiarism, fall in natural thinking abilities, too much reliance on AI, and the risk of inaccurate information. It is amazing that both sorts of academicians agree that training is important to make the greatest use of new skills. Finally, this study presents analytical insights into the extent of AI integration in EFL education in Bangladesh, revealing substantial gaps between public and private university views and offering options for further research and execution procedures.